Compliance anticorrupção e responsabilidade penal da pessoa jurídica (RPPJ): uma visão a partir da lógica de integridade nas relações público-privadas - Santana, Jaqueline Rosário (2021)
Integrity or anti-corruption compliance programs are part of a logic of coordination between public and private, forming a particular perspective of corruption and the ways in which it is dealt with. Its foundations emerge from an Anglo-Saxon context, legally and structurally distant from the reality of the Global South - Latin America, and spread through international organizations that enunciate the need for alignment between countries in the implementation of measures to combat and prevent practices corrupt. In this scenario, the growing incentive for the adoption of compliance systems by companies that interact with the public sector and their use in the conformation of corporate responsibility has been questioning the relevance of this responsibility in the penal modality. Thus, this study starts from the following question: according to the logic of adopting integrity programs in public-private relations does Corporate Criminal Liability (RPPJ) represent a condition of possibility for anti-corruption compliance? Searching for answers, the objective was to analyze the possible interdependence relationship of anti-corruption compliance with RPPJ, which is done methodologically guided by a dogmatic approach, insofar as it is understood that the construction of an object is, as well as any perception of the realities of the world, in dispute, however, we try to avoid epistemological digressions about these disputes. As the method of procedure, descriptive-comparative is used, since the study translates into observation, registration, analysis, correlation and comparison of the analyzed data, working with two referential realities. Furthermore, the study is essentially documental based on primary sources, in an accessory way it is configured as bibliographic-documental, and it is observed, in the format of final considerations, that, in the perspective of a logic / politics of integrity, in which it is inserted anti-corruption compliance and depending on its origins and premises for cooperation and prevention, the RPPJ does not necessarily represent a condition of possibility for this business mechanism - on the contrary, its subordination in response to a possibility of corporate accountability reduces it to an end in itself. An adequate incentive structure, on the contrary, in which suitable tools are guaranteed, mainly for cooperation, disincentive, prevention, reduction and detection of corrupt practices, such as regulatory simplification, information and awareness, as well as investment in agreements and proportional treatment to the behavior of the business actor, but also the effective punishment of corrupt practices, represented by administrative and civil liability in the context of LAC, a pragmatic choice in the face of controversies facing the criminal liability of legal entities, the inadequacy and inefficiency of the judiciary, proved to be more coherent as condition for the possibility of anti-corruption compliance and construction of a scenario of integrity in the interactions between public and private in Brazil.